Relaciones Internacionales en el siglo XXI: nueva dinámica de la seguridad a partir del enfoque sobrevivencia-dominación - Chacón Araya, Karen (2013)
The new world order shows concernfor global security as one of the biggest challenges facing States and other actors in the international system. On this basis the article underlines the generation of new paradigms in the discipline and the discussion of important theoretical debates; the articlea nalyzes the security dynamic from the survival-domination approach,through the peripheral, offensive and defensive realism. In order to deepenin the main proposition of these approaches,there were developed three case studies: United States, China and Argentina.